Co-sited and non co-sited coexistence analysis between IMT-Advanced and FWA systems in adjacent frequency band - A. Shamasn, Zaid (World Scientific And Engineering Acad And Soc, 2008)
In this paper, coexistence study of the future fourth generation IMT-Advanced with fixed wireless access systems is analyzed. Co-sited the two base stations and non co-sited coexistence and interference are investigated. The interference analysis model, adjacent channel interference ratio ACIR is applied in the band 3400-4200 MHz to extract the additional isolation needed to protect adjacent channel interference. Also interference to noise ratio as a standard interference criteria is introduced and possible engineering solutions are explained at last.